In situ simultaneous electrochemical ESR study of radicals generated from 2,2-dinitroethene-1,1-diamine (FOX-7). Intramolecular chemical exchange resulting in an alternation line-width effect - Šimková, Ludmila; Klíma, Jiří; Lušpai, Karol; Malček, Michal; Rockenbauer, Antal (Journal of magnetic resonance (San Diego, Calif., 2021)
The molecule of 2,2-dinitroethene-1,1-diamine (FOX-7) is one of the most interesting molecules with multiple redox centres stabilized by push-pull effect. To reveal the detailed mechanism of its electrochemical process radical intermediates formed in the course of its electrochemical reduction in organic aprotic media have been studied by in situ simultaneous electrochemical ESR measurements (SEESR). The radical generated on the second reduction step possesses an alternating line-width (AL) effect in the ESR spectra as a result of intramolecular dynamic processes in the timescale of ESR splitting constants. The spectra measured at different temperatures (230-335 K) were analysed with the help of a fitting program which includes a molecular dynamics. Observed dynamics describes well an asymmetric 2-site exchange model for the whole temperature range. With help of the optimized parameters and quantum chemical calculations this radical has been identified as 2,2-dinitroethane-1-amine-1-imine radical dianion, [(H2N)(HN)C=C(NO2)2]2-. The dynamic process responsible for the AL effect consists of mutual turning (changing of dihedral angle) of the both nitro groups, resulting in an intramolecular spin-density (electron) transfer. The dynamic parameters of the process have been established.
Keywords: Alternating line-width effect; EPR; ESR; In situ electrochemically generated radical; Temperature dependent ESR; FOX-7